ISLAMIC EDUCATIONAL VALUES IN THE ANIMATED FILM NUSSA - Ridhani Fizi (Fakultas Tarbiyah IAI Darussalam, 2025)
The current adult era, with the proliferation of technology, certainly has positive and negative sides. One of the phenomena that shows the negative side of the development of technology such as YouTube, Instagram, Twitter and Facebook is that many children use gadget media as a playmate, so that the child is not controlled in choosing content spread in cyberspace, as a result the child will be further away from religious values, humanitarian values, justice values and moral values. In this article, researchers describe the prevention of moral decadence for the younger generation, it is necessary to increase the role of education, especially the role of parents in choosing entertainment content that contains moral values for children. These efforts need to be made to prepare the next generation that has knowledge, faith and noble character. The writing of this article uses qualitative research with descriptive analysis. The author in this article uses Roland Barthes' semiotic analysis model known as the “two orders of signification” by looking for the denotation, connotation meaning of each scene. From the use of this method, researchers found that the animated film Nussa and Rarra, the episode of prayer is obligatory, contains the value of the concept of Islamic teachings, namely Akidah, Sharia and Akhlak. If parents are able to nurture and guide by choosing content that educates and implements it in life, it is expected that the children will be able to understand the values of Islam.